Profile of Bacterial Dermohypodermitis in Senegal over a 30-year period - Diallo M; Niasse M; Diatta BA; Diop A; Ndiaye M; Ly F; Dieng MT (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2017)
Introduction: The increase of both the frequency and severity of the bacterial dermohypodermitis (BDH) in Senegal suggests the existence of other risk factors outside of those classically known to be involved. Our study aimed to clarify the epidemiological, clinical and risk factors of BDH in Senegal.  Patients and methods: It was a retrospective, descriptive study based on records of all patients admitted for a DHD, in our department over a 30-year period (1982-2010). Results: We collected 456 cases including 365 erysipelas and 91 necrotizing bacterial dermohypodermitis (NBDH). Nearly 50% of cases were observed during the last decade. The sex ratio was 0.3 and 0.9 whereas the average age was 40 years and 45 years respectively for erysipelas and NBDH. It was a severe form of erysipelas in 243 cases and classical one in 122 cases. The predominant topography was the lower limb (81%). Simultaneous multifocal BDH was observed in 5 patients. The risk factors were skin bleaching (70%), venous insuffi ciency (37%), obesity (24%), a history of erysipelas (9.8%), lymphedema (9%) and pregnancy (3.5%). The portal of entry was identifi ed in 76% of the cases. NBDH was secondary to Vibrio vulnifi cus infection in 2 cases and Pasteurella multocida in one case. The outcome was recurrence of the disease (9%), death (2%) and elephantiasis (1.5%).  Discussion: Our study reports on of the the most important BDH series in Sub-Saharan Africa. It highlights a marked increase in the frequency of BDH in our our country over the last years. In general, the condition was severe and typically affected young adults between 35 and 45 years old, usually females and mostly practicing skin whitening.